Relevance of Hadith History of Imam al-Tirmidhī No. 1230 in Claw Machine Games - Hikmatul Izzah (Penerbit Hellow Pustaka, 2026)
Claw machines have become a popular form of modern entertainment in various shopping centers. However, the game's mechanism, which relies on uncertainty, often raises questions regarding its legal status from the perspective of Islamic jurisprudence (fiqh) regarding transactions, particularly regarding the element of gharar (intransitiveness). This study aims to analyze transaction practices in claw machine games through the Ma'ānī al-Ḥadīth approach, focusing on the prohibition of gharar as stipulated in the hadith narrated by Muslim. This article discusses the concept of gharar from an Islamic legal perspective and its relevance to modern gaming practices such as claw machines. In transactions, gharar arises when the contract contains elements of speculation and uncertainty, contrary to the principle of exchange contracts that require clarity of object, price, and time. The Prophet's hadith prohibiting the sale of